Critical factors of total quality management and its effect on performance in health care industry: A Turkish experience - (:unkn) unknown (LLC CPC Business Perspectives, 2005)
The literature on quality contains numerous case studies of successful companies and descriptions of quality concepts and quality improvement programs. The purpose of this study is to determine the critical factors of total quality management in the healthcare sector and to measure the effect of critical factors of total quality management on business performance in small and medium size hospitals in Turkey. The instrument used in this study was developed to identify critical factors (areas) of total quality management in the hospital industry. The technique of canonical correlation analysis is employed to investigate this relationship. To measure the eight dimensions of total quality management, thirty items were measured by using a five point Likert scale, ranging from "very low" to "very high". Performance of the hospital was measured using by subjective measures based on hospital administrators' perception of how their organization performed relative to the competition. Data analysis indicated a positive correlation between the performance of the hospital and the four critical factors of quality management in Turkish healthcare industry. © 2005 Yoser Gadhoum.
Keywords: Business performance; Canonical correlation; Total quality management